Pointwise polarization tensor bounds, and applications to voltage perturbations caused by thin inhomogeneities - Capdeboscq, Y; Vogelius, MS (IOS Press, 2006)
The main result of this paper establishes optimal pointwise bounds for the polarization tensors that appear in representation formulae for the voltage perturbations caused by low volume fraction inhomogeneities. Furthermore it is demonstrated how these pointwise bounds may be used to derive a particularly simple version of the representation formulae in the case of thin inhomogeneities. Copyright 2006 - IOS Press and the authors. All rights reserved.